Out of bounds reassessing the President's power to appoint elective officials (Philippine Law Journal, 2022)
In a democratic and republican State, the people should have the right to select their leaders via free, fair, and regularly scheduled elections. Unfortunately, recent laws and jurisprudence have enabled Congress to suspend elections in certain local govemment units ("LGUs") and use the resulting vacancies to authorize the president to appoint local elective officials. Postpone-and-appoint schemes, which are remnants of the martial law years in our current legal order, deprive the people of the opportunity to vote for their local leaders. The danger in leaving these arrangements unopposed is that they serve as open invitations for future congresses and presidents to come up with other seemingly legitimate reasons to justify suspending polls in other LGUs across the country. This Note assails the constitutionality of postpone-and-appoint schemes. It raises the following arguments: (1) the Appointments Clause does not cover elective officials; (2) the election of local officials is govered by specific rules under Article X of the 1987 Constitution, which precludes interference by national officials; (3) Congress's power of control over local government units does not entitle it to ignore the constitutional rules on elective officials; and (4) the president's power of general supervision does not include the power to appoint elective officials. Under the present Constitution, the people have reserved to themselves the power to directly choose who their local leaders should be. Neither Congress nor the president has the right to violate the sovereign's will.